Deposition of the stoichiometric coatings by reactive magnetron sputtering - Sagalovych, A.; Dudnik, S.; Sagalovych, V. (Физическая инженерия поверхности, 2012)
The investigations of the reactive magnetron depositing of the stoichiometric coatings “metal-metalloid” were done. The dependences between sputtering parameters of a target and processes of plasmochemical formation on the surface of sample “metal-metalloid” and formations of coatings of the appropriate structure were investigated. Experimental data on stoichiometric coatings AlN, Al₂O₃, TiN, TiO₂ is given. Features of reactive magnetron deposition and investigation results for obtaining of coatings with pregiven properties in particular for providing stability and controllability of coating deposition processes in time. Исследованы стехиометрические покрытия “металл-металлоид”, полученные реактивным магнетронным методом осаждения. Определены зависимости между параметрами распыления мишени и процессом плазмохимического осаждения на поверхность образца “металл-металлоид” при формировании покрытий соответствующей структуры. Приведены экспериментальные данные о стехиометрических покрытиях AlN, Al₂O₃, TiN, TiO₂. Определены особенности реактивного магнетронного напыления и получены результаты исследований относительно формирования покрытий с заранее заданными свойствами, в частности, для обеспечения устойчивости и управляемости процессов нанесения покрытий во времени. Досліджені стехіометричні покриття “метал-металоїд”, які отримані реактивним магнетронним методом осадження. Визначено залежності між параметрами розпилення мішені й процесом плазмохімічного осадження на поверхню зразка “метал-металоїд” при формуванні покриттів відповідної структури. Наведено експериментальні дані про стехіометричні покриття AlN, Al₂O₃, TiN, TiO₂. Визначено особливості реактивного магнетронного напилювання та отримані результати досліджень щодо формування покриттів із заздалегідь заданими властивостями, зокрема, для забезпечення стійкості й керованості процесів нанесення покриттів у часі.